From Manila to the world 10 stories, 10 cities, one accidental globe-trotter - Mangahas, Paolo (Espana, Manila, Philippines University of Santo Tomas Publishing House, 2022)
From Manila, to the world: 10 stories, 10 cities, one accidental globe-trotter is a compilation of stories from 10 different locations that are as much tales of self-discovery as they are adventures in new places. While it is a journey into rich cultures and landscapes, this book is also essentially a journey within, presented in Mangahas’ sometimes wry, occasionally hilarious, yet always authentic voice. --Back cover.
These stories, which smoothly juxtapose Mangahas’ epiphanies on personal growth with observations of different cultures, will inspire readers to not just get up and go, but to be more introspective about life, people, and the world—and to discover the humor and wisdom always waiting in unexpected places. -- Back cover.
1: Manila: Boxes -- 2: Kuala Lumpur: False advertising -- 3: Moscow: Cracked ice -- 4: Galapagos: Survival of the fittest -- 5: Hanoi: No ordinary day -- 6: New York: Freakuency -- 7: Istanbul: Decisions, decisions -- Las Vegas: That thing about fear -- 9: Suva: Sensory perceptions and fairy tales -- 10: Singapore: Living large with little.
Keywords: Mangahas, Paolo -- Travel; Filipinos -- Travel; Voyages and travels